PENGGUNAAN TAHAN JENIS LEMPUNG COKLAT, TUFFASIUS DAN LEMPUNG HITAM SEBAGAI BAHAN TIMBUN TANGGUL - Djoko Subari (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2001)
Levee is appereances flood control construction wich is mean to more larges of section of river. The material of tuffaceous clay and brown clay beside black clay which were the material distributing in the constructing can be planned as levee embankment. Levee embankmen must be compected as well as due to does not erotion ang pipings. The investigation materials to be constructedÂ while to be layer and whole constructed of levee embankmet as specification on laboratories test and trial embankmen. The test aims to fine out the suitable compaction method such as kind of compaction equipment, Placement thickness and number of passage and also to obtain the useful data to supplement technical provision for levee embankment work. The test location, cases of compsaction method, test items, test quantities and test procedure are referred to the technical specification for levee embankment.